This commit is contained in:
Claudio Maggioni 2021-05-28 18:16:54 +02:00
parent 43f54092d6
commit cd83872124
2 changed files with 5 additions and 4 deletions

View File

@ -217,7 +217,7 @@ $$L(x, \lambda) = c^T x - \lambda^T (Ax - b) - s^T x$$
The KKT conditions are the following:
1. The partial derivative of the lagrangian w.r.t. $x$ is 0:
$$\nabla_x L(x, \lambda) = c - A^T \lambda - s = 0 \Leftrightarrow A^T \lambda
$$\nabla_x L(x, \lambda, s) = c - A^T \lambda - s = 0 \Leftrightarrow A^T \lambda
+ s = c$$
2. Equality constraints hold:
$$Ax - b = 0 \Leftrightarrow Ax = b$$
@ -233,7 +233,8 @@ The KKT conditions are the following:
We define the dual problem is the following way:
$$\max b^T \lambda \;\; \text{ s.t. } \;\; A^T \lambda \leq c \;$$
$$\max b^T \lambda \;\; \text{ s.t. } \;\; c - A^T \lambda \geq 0
\Leftrightarrow A^T \lambda \leq c \;$$
We then introduce a slack variable $s$ to find the equality and inequality
constraints:
@ -250,12 +251,12 @@ $$\min - b^T \lambda \;\; \text{ s.t. } \;\; A^T \lambda + s = c \; \text{ and
We then compute the Lagrangian of the dual problem:
$$L(\lambda, x) = -b^T \lambda + x^T (A^T \lambda + s - c) - x^T s = - b^T
$$L(\lambda, x, s) = -b^T \lambda + x^T (A^T \lambda + s - c) - x^T s = - b^T
\lambda + x^T (A^T \lambda - c)$$
The KKT conditions are the following:
1. The partial derivative of the lagrangian w.r.t. $x$ is 0: $$\nabla_{\lambda}
1. The partial derivative of the lagrangian w.r.t.\ $\lambda$ is 0: $$\nabla_{\lambda}
L(\lambda, x) = - b^T + x^T A^T = 0 \Leftrightarrow Ax = b$$
2. Equality constraints hold: $$A^T \lambda + s = c$$
3. Inequality constraints hold: $$c - A^T \lambda \geq 0 \Leftrightarrow s \geq